THE ROLE OF IRON FOLIC ACID AND MULTIPLE MICRONUTRIENTS IN TYPE OF CHILDBIRTH DELIVERY: ECONOMIC AND HEALTH IMPLICATION - NAJMIATUL FITRIA; SARAH PUTI AMALIA; AFIFAH MACHLAURIN; HANSEN NASIF (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Pregnancy is a critical period that can pose nutritional challenges, such as chronic energy deficiency and anemia, increasing maternal mortality risk. The World Health Organization recommends iron and folic acid supplements to mitigate these risks. This study compared labor types and associated costs between iron-folic acid (IFA) and multiple micronutrient (MMN) supplementations during pregnancy. Methods: An economic evaluation was conducted retrospectively at Semen Padang Hospital, analyzing data from January to December 2021. A total of 201 pregnant women were included, with 128 undergoing cesarean delivery. Cost data were collected from the hospital’s perspective and analyzed to identify differences between supplementation groups. Results: Total direct costs did not differ significantly between the IFA and MMN groups (p=0.82). However, medical costs varied substantially, with cesarean delivery costs being approximately 5 times higher than normal delivery costs. Conclusion: This study emphasizes the economic burden of cesarean deliveries compared to normal births and highlights the need for further evaluation of micronutrient supplementation’s cost-effectiveness. Findings advocate for policies that optimize maternal health outcomes and reduce delivery-related costs, addressing the high incidence of elective cesarean sections.